Role of fungi in fruit rot and immature nut fall of coconut - S. Venugopal; R. Chandra Mohanan (International Coconut Community, 2006)
The incidence of fruit rot and immature nut fall is on the increase in southern districts of Kerala state, India, ever since the intensity of eriophyid mite (Aceria guerreronis Keifer) infestation increased in this part of the country. Hence, nut samples were collected from 8 southern districts of Kerala state and studies were undertaken to find out the role of fungi in fruit rot of mite infested coconut. Out of 577 samples of coconuts at various stages of development, button to mature nuts, collected from different locations, 445 samples yielded fungi. Lasiodiplodia theobromae Pat., a wound pathogen was found to be the major fungus causing fruit rot and immature nut fall in coconut. The fungus enters the tissue through wounds caused by eriophyid mite in the soft tissue beneath perianth. When nearly mature /mature nuts were infected the infection spread internally into mesocarp without any external lesion or with a minute lesion on the husk surface. Infection in mature nuts continued to spread internally during storage causing rotting of kernel. Phytopthora fruit rot was observed only in Idukki district with high rain fall and humidity. Fruit rot caused by L. theobromae was found in all 8 southern districts of Kerala throughout the year. Thielaviopsis paradoxa, Colletotrichum gloeosporioides, and Fusarium sp. were also isolated from the lesions on few samples of tender nuts. But, at present they were only minor pathogens associated with rotting of young nuts.